Obstetric and neonatal outcome in women with a history of recurrent miscarriage at tertiary care hospital, Karnataka: a retrospective cross-sectional study - Upadhyay, Chintan; Upadhyay, Nisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: When clinical pregnancy is established, the risk of spontaneous pregnancy loss is ~12-14%, and therefore the incidence of Recurrent Pregnancy Loss (RPL) by chance alone would be in the order of 0.35%. It occurs in 0.5-3% of women. The objective of this study was to evaluate the obstetric outcome in pregnancies with history of one or more abortions. Methods: It is a retrospective cross-sectional study done at Obstetrics and Gynecology Department, Dr. B. R. Ambedkar Medical College and Hospital, Bangalore. Record review of cases was done from January 2005 to December 2009. Inclusion criteria were pregnancies with history of previous abortions. Results: There were 400 cases with previous history of abortions. There were 266 (66.4%) booked cases while 134 (33.5%) were unbooked cases. 272 (68.0%) patients crossed viable period of pregnancy (more than 28 weeks). Around 56 (14.0%) cases had repeat abortions, 276 (69.0%) cases underwent vaginal delivery and 124 (31.0%) underwent cesarean section. Almost 91 (22.8%) of Babies were low birth weight while others were above 2.5 kg. There were 52 (13.0%) preterm babies and 28 (7.0%) Intrauterine demise of fetuses. Conclusions: Patients with previous history of abortions are at increased risk of adverse maternal and perinatal outcome.